MODEL HUBUNGAN ANTARA BIROKRASI DAN POLITISI DI INDONESIA - Fakhruddin, M. Anas (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2012)
Bureaucracy plays an important role in the formulation, implementation and monitoring of public policies, as well as in the evaluation of their own performance. In this strategic position, there is always an effort to attract the bureaucracy in the political game area. Bureaucracy used to attain, maintain, or strengthen the power. There are three models to describe the relationship of bureaucracy and politicians: the relationship where the government/executive’ power is dominant that it could dictate the legislative/political/parliamentary, the relationship which the legislators and politicians have always crossed into the realm of the executive and impose their will, and the therelationship which the executive and legislative branches tend to look for a balanced position. Therefore, the government bureaucracy both directly or indirectly related to political interest groups.